Diurnal Variability in Aeolian Sediment Transport at Gale Crater, Mars. Issue 2 (15th February 2022) - Baker, Mariah M.; Newman, Claire E.; Sullivan, Robert; Minitti, Michelle E.; Edgett, Kenneth S.; Fey, Deirdra; Ellison, Doug; Lewis, Kevin W.
Abstract: A suite of high resolution cameras onboard the Mars Science Laboratory (MSL) Curiosity rover have provided an unparalleled look at active aeolian processes on Mars, including within the first active dune field explored on another planet, the Bagnold Dunes. Here we present results from a subset of MSL's repeat imaging ("change detection") experiments with temporal resolutions sufficient to probe the diurnal variability in winds within Gale crater. Images reveal that saltation is a near‐daily phenomenon during southern summer, with repeatable diurnal circulation patterns producing steady impact ripple migration toward the west/southwest. Nighttime fluxes are inferred to be ∼four times larger than daytime fluxes, consistent with predictions from the MarsWRF model of multiple periods of enhanced wind between sunset and sunrise. Multiple factors are likely facilitating saltation at this time: (a) time‐averaged nighttime winds have a higher degree of variance (i.e., higher peak friction speeds) than daytime winds, (b) interactions between regional Hadley flows and local, thermally driven slope winds cause increased turbulence at night, and (c) relatively higher atmospheric density produces correspondingly higher shear stresses and decreases critical thresholds. Observations of sand transport at a range of spatiotemporal scales (down to scale of individual particles moving on the timescale of seconds) support the idea that bedform migration is driven by intermittent, low‐flux saltation events when winds fluctuate between canonical impact and fluid thresholds. Yet, whereas gustiness may play a role in initiating transport, saltation is found to be highly predictable on diurnal timescales and is only stochastic on the shortest timescales characteristic of turbulent fluctuations in wind. Plain Language Summary: Repeat "change detection" imaging experiments performed using cameras onboard the Mars Science Laboratory Curiosity rover have provided a rare look at active wind‐blown sand movement on Mars. Rover images acquired during local summer reveal near‐daily migration of sand ripples toward the west/southwest. Ripple migration is inferred to occur predominately between sunset and sunrise each sol, based on the observation of ∼four times more sand transport at night than during the day. In lieu of in situ meteorological data, predictions from the MarsWRF atmospheric model are used to interpret the circulation patterns responsible for sand transport. Close comparison between the model and observations suggests that dunes and ripples in the vicinity of the rover's traverse are being shaped by a unique combination of regional circulation patterns and local slope winds. Close examination of sand movement (down to the scale of individual sand grains) helps shed light on the physics of sand transport under natural Martian conditions and decipher possible differences between wind‐driven landscape modification on Earth and Mars. Key Points: Curiosity rover images have enabled the examination of aeolian transport on smaller spatiotemporal scales than achieved previously on Mars Recurring nighttime circulation patterns generate near‐daily impact ripple migration along the rover's traverse during local summer Ripple morphodynamics are consistent with intermittent, low‐flux saltation driven by winds between traditional impact and fluid thresholds